Long-term results of radiofrequency and microwave ablation of colorectal cancer liver metastasis - Ahmet Gürkan Erdemir; Sevilay Karahan; Emre Ünal; Türkmen Turan Çiftçi; Devrim Akıncı; Şuayib Yalçın; Okan Akhan (International Journal of Gastrointestinal Intervention, 2023)
Background : : Radiofrequency ablation (RFA) or microwave ablation (MWA) is effective for colorectal cancer liver metastases. We aimed to investigate the impact of different variables on survival. Methods : : Sixty-four patients (142 lesions) who underwent thermoablation between January 2007 and January 2019 were retrospectively analyzed. The overall survival (OS) and liver progression-free survival (Li-PFS) were compared using Kaplan-Meier analysis. Univariable and multivariable Cox-regression were done to identify prognostic factors. Results : : No significant difference was found between median OS (59.39 months) and Li-PFS (41.22 months) of patients who received MWA (n = 33); and median OS (61.00 months) and Li-PFS (53.43 months) of patients who received RFA (n = 31) (OS: P = 0.697; Li-PFS: P = 0.122). The median OS and Li-PFS were significantly decreased with lung metastases and K-ras mutations (P < 0.001). There was no correlation between prior systemic chemotherapy (n = 25) and both outcome parameters (OS: P = 0.613; Li-PFS: P = 0.665). No significant difference was observed in patients with lesions less than 30 mm diameter (n = 44) whether they received prior systemic chemotherapy (n = 17) or not (n = 27) (OS: P = 0.27; Li-PFS: P = 0.42). Similarly, in patients with a lesion of 3-5 cm diameter (n = 20; eight of them had prior chemotherapy), there was no correlation for both outcomes (OS: P = 0.069; Li-PFS: P = 0.71). The most important prognostic factor was concomitant lung metastases (hazard ratio = 3.689, P = 0.002). Conclusion : : Concomitant lung metastasis and mutant K-ras were associated with shorter survival. Survival did not differ significantly regarding thermoablation technique or prior systemic chemotherapy. However, in the patient group with lung metastases, curative treatments had better survival than patients who received chemotherapy only. Additional therapeutic options should be considered in patients with concomitant lung metastasis.